Nursing protocol for children with sickle cell disease in emergency room: a convergent-care approach - Juliane Batista Costa Teixeira; Aisiane Cedraz Morais; Viviane Euzébia Pereira Santos; Deisy Vital dos Santos; Evanilda Souza de Santana Carvalho; Juliana de Oliveira Freitas Miranda; Luana Santana Brito; Lucas Amaral Martins (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: to describe the methodological process of developing a nursing care protocol for children with sickle cell disease in the emergency room. Method: convergent care research, carried out in a public pediatric hospital in the state of Bahia, with 12 emergency nurses specialist. Data production took place between July 2020 and April 2021, with semi-structured interviews, observation in a field diary and convergence groups, according to the research phases: conception, instrumentation, scrutiny and analysis. Results: The final result was the construction of a nursing care protocol for children with sickle cell disease in the emergency room for use in the study field. Final considerations: the Convergent Care Research proved to be an excellent methodological procedure for intervention in the health service, whose nursing care protocol was based on the reflections of professionals on evidence-based practices, whose consensus can enable safe and quality care.